Transformar, transtornar e transceder: percepções de profissionais da educação sobre identidade de gênero e nome social da pessoa transgênero - Acioles, Marcossuel Gomes (2023)
Transform, upset and transcend: perceptions of education professionals about gender identity and social name of the transgender person, arises from the interest in developing strategies through intervention research that would allow access to the perceptions of education professionals about gender identity and use of social name of transgender people and through the Freirian method of the culture circle we could develop dialogues that would impact the participants' understanding regarding the agenda being worked on. The research was developed in the interior of Ceará, specifically at the Federal Institute of Ceará (IFCE), Itapipoca campus, with the participation of 6 members working in the educational context. Data analysis was carried out through Bardin's content analysis, which allowed us to arrive at three categories, named as follows: TRANSform: Gender identity and social name, school in culture and culture in school; TRANStornar: open paths and closed paths and TRANScender: “There is no lack of programs, there is a lack of participation and ethical commitment”, in these there are explanations that reflect the debates that took place in the culture circle, advances and weaknesses in the face of issues involving transgender people in the school space. It is considered that social transformations, the formulation of laws, guarantee a change in the approach to transgender people, however, prejudice, oppression and gender violence are still experienced in different nuances and the non-participation of professionals in spaces for debate on the topic can be evidence to prove the facts.